Laparoscopic pancreas-preserving near total duodenectomy for large villous adenoma in patients with total colectomy for familial adenomatous polyposis - Jung, Dawn; Jung, Ji Eun; Kang, Chang Moo (Journal of minimally invasive surgery, 2023)
Most familial adenomatous polyposis (FAP) patients undergo total colectomy, but duodenal polyposis develops in up to 90% of patients with FAP and a 4% to 18% risk of duodenal and ampullary cancer remains. Laparoscopic pancreas-preserving near total duodenectomy is thought to be a potential option and can be an effective approach to preserve the pancreas. A 48-year-old male patient, who underwent laparoscopic total colectomy with end ileostomy because of FAP with colorectal cancer, was diagnosed with a 20 mm-sized duodenal adenoma in the second to the third portion. The operation was performed on December 27, 2021. Near total duodenectomy was done and type II Billroth gastrojejunostomy was done. Laparoscopic pancreas-sparing duodenectomy is shown to be safe, with favorable short-term oncologic outcome compared to laparoscopic pancreatoduodenectomy in terms of less blood loss, faster recovery time, and much less total cost.